Development of Virtual Reality Endogen Energy (VREE) Media for Physics Learning Mechanical Wave on Class XI - Anisa Kartikasari; Mita Anggaryani (IKIP Mataram, 2022)
Computer Virtual Reality (VR) is another innovation in the realm of training that is applied to the educational experience. The improvement of VR innovation in the field of training has experienced a few issues. This study creates learning media in view of VR innovation created by MilleaLab. MilleaLab is a phase for making VR media with extra specific components to make a fair impression of reality to help the educating and developing experience. The headway of VR media which is named